Inhibition of Calotropis procera Latex-Induced Inflammatory Hyperalgesia by Oxytocin and Melatonin. Issue 6 (14th December 2005) - Padhy Padhy, Biswa M. Biswa M.; Kumar Kumar, Vijay L. Vijay L.
Abstract : The latex of the wild growing plant Calotropis procera produces inflammation of the skin and mucous membranes upon accidental exposure. On local administration it elicits an intense inflammatory response due to the release of histamine and prostaglandins that is associated with hyperalgesia. In the present study we have evaluated the anti-inflammatory and antinociceptive activity of oxytocin and melatonin against rat paw edema induced by dried latex (DL) of C procera and compared it with that against carrageenan-induced paw edema. Aqueous extract of DL of C procera or carrageenan (1% ) was injected into the subplantar surface of the rat paw and the paw volume was measured at 0, 1, 2, 3, 4, 6, 10, and 24 hours. The associated hyperalgesic response and functional impairment were also evaluated concomitantly by dorsal flexion pain test, motility test, and stair climbing ability test. The inhibitory effect of oxytocin and melatonin on edema formation and hyperalgesic response was compared with dexamethasone. DL-induced edema formation was maximum at 2 hours and was associated with decreased pain threshold and functional impairment. Treatment with melatonin significantly attenuated the edematous response while both oxytocin and melatonin increased the pain threshold and improved functional parameters. Both oxytocin and melatonin significantly inhibited the hyperalgesia associated with DL-induced paw edema. Oxytocin was found to be as effective as melatonin in ameliorating the hyperalgesic response. However, it was found to be less effective than melatonin in attenuating edema formation.